O papel, a importância e os desafios do pedagogo em espaços não escolares: experiência sobre o estágio curricular na defensoria pública - Bezerra, Daiane Araújo Aquino (Universidade Federal do Tocantins, 2022)
The present Work of Completion of Degree in Pedagogy deals with the role of the pedagogue in non-school spaces and has as main objective to understand how the work of the pedagogue in non-school spaces, its importance and challenges, from the narrative autobiographical, of experiences of the curricular internship in the Public Defender's Office of the city of Tocantinópolis/TO, of a pedagogue in training. To achieve the objectives of this study, we opted for a qualitative methodology with bibliographic research and narrative research, having the autobiographical narrative as a methodological strategy and also with data source research. The construction of the narrative and the return to the internship experiences in the advocacy based on the literature end up revealing that the internship experiences in a non-school space were significant to understand the dimension of the scope of the pedagogue's performance and training to become a qualified professional in a career face challenges of social prestige and is undervalued. At the same time its importance and challenges for acting in non-school spaces. It is concluded that the role of a pedagogue in spaces such as the public defender's office is important due to the specificity of this professional in dealing with children, young people and adults and in the focus of their work, but it also requires a lot of preparation, good training for the follow-up work. , guidance and assistance for children who are referred to the Public Defender's Office of Tocantinópolis –TO, as well as dealing with their relationship with their families and with the school.